Characteristics of Stress Transfer and Progressive Fracture in Overlying Strata due to Mining-Induced Disturbances - Xiang-feng Lv; Hong-yuan Zhou; Ai-wen Wang; Chun Feng; Xiao-chun Xiao (Advances in Civil Engineering)
In this study, based on the mining of the 13210 working face in the Yima coal mine of the Gengcun village, China, a simplified mechanical model for the analysis of dynamic destabilization of the overlying strata during underground mining was constructed. The numerical simulation was used to analyze the stress patterns in the advanced abutments of the tunnel face and the characteristics of dynamic failures in the overlying strata. Furthermore, similitude experiments were conducted to study the process of stress release and deformation in the overlying strata, and to analyze the effects of overburden destabilization on the ground surface settlement. The theoretical analysis indicated that if the geometric parameters of a working face are fully determined, a stiffness ratio no greater than 1 is required for dynamic destabilization to occur. The numerical simulation results show that the stress in the overlying strata decreases with a decrease in distance from the tunnel face. The stresses in the advanced abutments initially increase with an increase in distance from the tunnel face, followed by a decrease in stress, and an eventual stabilization of the stress levels; this corresponds to the existence of a “stress build-up zone,” “stress reduction zone,” and “native rock stress zone.” In similitude experiments, it was observed that a “pseudoplastic beam” state arises after the local stresses of the overlying strata have been completely released, and the “trapezoidal” fractures begin to form at stress concentrations. If the excavation of the working face continues to progress, the area of collapse expands upward, thereby increasing the areas of the fracture and densification zones. Owing to the nonuniform settlement of the overlying strata and the continuous development of bed-separating cracks, secondary fractures will be generated on both sides of the working face, which increase the severity of the ground surface settlement.